Analisis Kepatuhan Wajib Pajak terhadap Penggunaan E-Filing dengan Pendekatan Technology Accetance Model (TAM) di Wilayah Blitar - Susanti, Diva; Fristiani, Nosilia (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to explain the relationship between perceived usefulness and ease of use on the influence of taxpayer compliance using the E-Filing application. In addition, this study also evaluates the role of using the E-Filing application as an intervening variable between perceived usefulness and perceived ease of use on taxpayer compliance. This research method uses a quantitative approach by distributing questionnaires to Taxpayers via Google Form containing statements of agreement or disagreement with the statements in the questionnaire. The questionnaire was distributed to Taxpayers who had used the E-Filing tax application system in the Blitar area. Data were analyzed using IBM SPSS 26 and IBM AMOS 20. The results of this study are expected to provide an understanding of tax application users and provide knowledge for application developers about the factors that must be developed in the application to make it easier to accept and use.